The impact of drugs on male fertility: a review. (16th June 2017) - Semet, M.; Paci, M.; Saïas‐Magnan, J.; Metzler‐Guillemain, C.; Boissier, R.; Lejeune, H.; Perrin, J.
Summary: Beside cytotoxic drugs, other drugs can impact men's fertility through various mechanisms. Via the modification of the hypothalamic–pituitary–gonadal axis hormones or by non‐hormonal mechanisms, drugs may directly and indirectly induce sexual dysfunction and spermatogenesis impairment and alteration of epididymal maturation. This systematic literature review summarizes existing data about the negative impact and associations of pharmacological treatments on male fertility (excluding cytotoxic drugs), with a view to making these data more readily available for medical staff. In most cases, these effects on spermatogenesis/sperm maturation/sexual function are reversible after the discontinuation of the drug. When a reprotoxic treatment cannot be stopped and/or when the impact on semen parameters/sperm DNA is potentially irreversible (Sulfasalazine Azathioprine, Mycophenolate mofetil and Methotrexate), the cryopreservation of spermatozoa before treatment must be proposed. Deleterious impacts on fertility of drugs with very good or good level of evidence (Testosterone, Sulfasalazine, Anabolic steroids, Cyproterone acetate, Opioids, Tramadol, GhRH analogues and Sartan) are developed.